Empowering Health: Unveiling the Impact of Self-Efficacy and Lifestyle on Hypertension Management - Mega, Juli Yosa (Utan Kayu Publishing, 2024)
This study aims to investigate the significant relationship between self-efficacy and lifestyle on the prevalence of hypertension. In this context, self-efficacy is defined as an individual's belief in managing blood pressure through health behaviors, while an unhealthy lifestyle includes habits such as a high-salt diet and minimal physical activity. This research utilized a quantitative method with a descriptive correlational design and a cross-sectional approach. Out of 70 respondents, it was found that 27 individuals (38.6%) had sufficient self-efficacy, 36 individuals (51.4%) demonstrated an unhealthy lifestyle, and 37 individuals (52.9%) suffered from hypertension. Statistical analysis showed a significant relationship between self-efficacy (p-value = 0.000) and lifestyle (p-value = 0.000) with the incidence of hypertension. These results support the theory that enhancing self-efficacy and shifting towards a healthier lifestyle can reduce the risk of hypertension, providing significant contributions to the literature and practices in hypertension management. Abstrak: Studi ini bertujuan untuk menginvestigasi hubungan yang signifikan antara self-efficacy dan gaya hidup terhadap prevalensi hipertensi. Dalam konteks ini, self-efficacy diartikan sebagai keyakinan individu dalam mengelola tekanan darah melalui perilaku kesehatan, sedangkan gaya hidup tidak sehat mencakup kebiasaan seperti diet tinggi garam dan minim aktivitas fisik. Penelitian ini menggunakan metode kuantitatif dengan desain deskriptif korelasional dan pendekatan cross-sectional. Dari total 70 responden, ditemukan bahwa 27 orang (38,6%) memiliki self-efficacy yang cukup, 36 orang (51,4%) menunjukkan gaya hidup tidak sehat, dan 37 orang (52,9%) menderita hipertensi. Analisis statistik menunjukkan hubungan yang signifikan antara self-efficacy (p-value = 0,000) dan gaya hidup (p-value = 0,000) dengan kejadian hipertensi. Hasil ini mendukung teori bahwa peningkatan self-efficacy dan perubahan ke arah gaya hidup yang lebih sehat dapat mengurangi risiko hipertensi, memberikan kontribusi penting terhadap literatur dan praktik dalam manajemen hipertensi.